Serological and histopathological survey of Lawsonia intracellularis infection in 30 argentinean swine herds - Machuca, Mariana A.; Cappuccio, Javier A.; Piñeyro, Pablo E.; Venturini, Maria C.; Quiroga, Maria A.; Perfumo, Carlos J. (Brazilian Journal of Veterinary Pathology, 2009)
The objectives of this work were: 1) to investigate L. intracellularis antibodies in grower-finisher pigs from 30 herds by immunofluorescent antibody test (IFAT) 2) to evaluate the porcine proliferative enterophaty (PPE) lesions by histopathology, histochemistry (Warthin Starry) and immunohistochemistry (IHC) in ileum samples obtained at slaughterhouse from 10 selected herds, 9 seropositive and 1 control seronegative. At each farm, 30 grower-finisher pigs (18 to 20 weeks old pigs) were randomly selected for blood sampling. The sera were analyzed with a commercial IFAT kit (IleiTest, Elanco Animal Health). The overall percentage of positive pigs was 31.2% (281/900), whereas the percentage of positive farms was 76.7% (23/30). The within-herd mean percentage of positive sera ranged from 27.5 to 53.6%. Only 1 out of the 10 selected farms showed characteristic gross and histopathological lesions at slaughterhouse. On the other hand, 4 farms were positive by immunohistochemistry . In conclusion L. intracellularis infection is widespread among Argentinean farms even though the within-herd percentage was quite variable. Slaughter pigs without microscopic lesions showed immunoreactivity to L. intracellularis.